Potential of ultrasound investigation in diagnostics of pseudomembranous colitis in surgical patients - O. A. Alekseyechkina; E. Ya. Dubrov; Ye. S. Vladimirova; T. P. Pinchuk; G. P. Titova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Improvement of diagnostics of pseudomembranous colitis.Material and methods. Ultrasound signs of pseudomembranous colitis (PMC) received by comparison of ultrasound, endoscopic, clinical and morphological data in 64 patients aged from 24 to 76 years were presented. Patients admitted with suspicion to acute abdominal surgical pathology. Abdominal ultrasound was carried out according to standard procedure with assessment of disintegration of peritoneal layers, state of all parts of the large intestine, loops of small intestine and its mesentery were examined.Results. Set of ultrasound signs, according to which it is possible to suspect pseudomembranous colitis is determined: thickening and lamination of walls of the large intestine, paracolic edema, free fluid in abdominal cavity, depositions of fibrin on parietal and visceral peritoneum. Sensitivity of the test was 95%, specificity – 47%, accuracy – 84%.Conclusions. The ultrasound method can be applied as one of the first and available methods of revealing of PMC signs at severe patients receiving massive antibacterial treatment. This method allows to carry out dynamic control of the course of disease, is well-timed to reveal its complications, to control efficacy of specific treatment.